Genetic Versus Epigenetic BRCA1 Silencing Pathways: Clinical Effects in Primary Ovarian Cancer Patients. Issue 8 (1st October 2017) - Sun, Tingting; Ruscito, Ilary; Dimitrova, Desislava; Chekerov, Radoslav; Kulbe, Hagen; Baron, Udo; Blanchard, Véronique; Panici, Pierluigi Benedetti; Darb-Esfahani, Silvia; Sehouli, Jalid; Olek, Sven; Braicu, Elena Ioana
Abstract : Objectives: The aim of the present study was to assess in a large cohort of primary epithelial ovarian cancer patients the incidence and the clinical effect of BRCA1 genetic and epigenetic silencing mechanisms. Methods: A total of 188 primary epithelial ovarian cancer patients, treated between 2000 and 2011 at the Charité University Hospital of Berlin, were included. The patients' tumor and blood samples were obtained from the Tumor Bank Ovarian Cancer Network (www.toc-network.de ). Direct sequencing of BRCA1 exon 11 was performed to detect germline mutations, whereas tumor samples were assessed for BRCA1 promoter hypermethylation by bisulphite-converted methylation-specific polymerase chain reaction. Basing on their BRCA1 status, patients were compared regarding clinicopathological variables and survival. Results: Twenty-one patients (11.2%) showed hypermethylation in BRCA1 promoter (HMB), and 18 patients (9.6%) presented germline mutations in BRCA1 exon 11 (GMB). Patients with HMB showed a significantly younger age at diagnosis compared with BRCA1 wild type (BWT) patients (54 vs 61 years, P = 0.045), and both GMB and HMB patients were more likely to have high-grade serous ovarian cancer (76.2% and 77.8% vs 52.7%, P = 0.043 and P = 0.043). Positive family history of breast or ovarian cancer (OC) was more frequently reported among GMB patients with respect to BWT patients (44.4% vs 13.5%, P = 0.003); GMB, HMB, and BWT patients did not show significant differences in terms of tumor dissemination pattern, surgical outcomes, platinum response or survival; neither mutational nor hypermethylation BRCA1 status was found to be an independent prognostic factor for OC patients. Conclusions: Hypermethylation in BRCA1 is associated with earlier occurrence of OC. In addition, the coexistence of both GBM and HMB is an infrequent event, occurring in 0.5% of OC cases. Silencing of BRCA1 through mutation and hypermethylation confers to distinct clinical characteristics of OC patients but similar clinical outcome with respect to BWT patients.